Determining Auspicious Days for Weddings and Circumcisions in Kuta Traditional Village - Prabawati, Mega Nur; Mulyani, Eva; Muslim, Siska Ryane (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini menyelidiki filosofi dan aktivitas matematika yang tertanam dalam menentukan hari baik untuk upacara pernikahan dan khitanan di Desa Adat Kuta. Dengan menggunakan metode penelitian kualitatif dengan pendekatan etnografi, pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi terhadap tokoh adat, tetua adat, dan anggota masyarakat. Temuan ini mengungkapkan enam aktivitas matematika mendasar yang selaras dengan nilai-nilai budaya lokal: penghitungan (digunakan untuk menghitung kesesuaian dan menentukan hari baik), penempatan (untuk mengidentifikasi tanggal terlarang dan posisi spasial), pengukuran (untuk mengurutkan hari dan menyelaraskan waktu), perancangan (untuk mengatur tanggal dan waktu menurut adat istiadat), bermain (mengamati aturan dan menafsirkan hasil), dan menjelaskan (memberikan interpretasi perhitungan yang bermakna). Studi ini menunjukkan bahwa praktik etnomatematika ini tidak hanya mendukung tradisi lokal tetapi juga memperkuat identitas budaya dan warisan masyarakat Kuta. Integrasi konsep matematika seperti penjumlahan, pembagian, modulo aritmatika, dan barisan aritmatika dalam kebiasaan ini mengungkapkan hubungan rumit antara matematika dan praktik budaya, menawarkan perspektif unik untuk pendidikan matematika yang responsif terhadap budaya. This study investigates the philosophy and mathematical activities embedded in determining auspicious days for marriage and circumcision ceremonies in Kuta Traditional Village. Employing qualitative research methods with an ethnographic approach, data were gathered through observations, interviews, and documentation from traditional leaders, elders, and community members. The findings reveal six fundamental mathematical activities that align with local cultural values: counting (used in calculating compatibility and determining favorable days), locating (for identifying restricted dates and spatial positions), measuring (for sequencing days and aligning timings), designing (for organizing dates and times according to customs), playing (observing rules and interpreting outcomes), and explaining (providing meaningful interpretations of calculations). This study demonstrates that these ethnomathematical practices not only support local traditions but also reinforce the cultural identity and heritage of the Kuta community. The integration of mathematical concepts such as addition, division, modulo arithmetic, and arithmetic sequences within these customs reveals the intricate relationship between mathematics and cultural practices, offering a unique perspective for culturally responsive mathematics education. Keyword: Ethnomathematic; philosophy; mathematical activities; goodday of marriage and circumcision.